Nord Stream 2 - Germany's dilemma - Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2021)
The Nord Stream 2 project presents the German government with the dilemma of choosing between energy and foreign policy interests. Geopolitical arguments often prevail in the political discourse. Yet, a weighing of priorities requires a look at the energy policy context, too. When it comes to balancing interests, there are no easy or 'cheap' answers. With a focus on the energy context, it has to be emphasized that a cooperative approach toward energy transformation promises the greatest dividend for a balance of interests, but it presupposes a minimum consensus within the European Union (EU), along with the United States (US), Ukraine, and Russia.
Keywords: 320